Haul Sheikh Burhanuddin Ulakan in the Basapa Tradition of the Ulakan Community of Padang Pariaman - Amril Amril; Neneng Kapitri; Endrika Widdia Putri; Efendi Efendi (Al Qalam, 2023)
This article aims to explain the Basapa tradition presented in this type of qualitative research. The data collection methods used are observation, interviews and documentation. Then the data obtained was analyzed using descriptive, interpretive and analytical methods. The Basapa tradition is a tradition to commemorate the death of a figure who propagated Islam in Minangkabau as well as the carrier of the Syatariyyah order to Minangkabau, namely Sheikh Burhanuddin Ulakan which is held every Wednesday after the 10th day of the month of Syafar. The rituals and processes of the Basapa tradition that are carried out include; pilgrimage together; Buraha prayer; and dhikr or recite tahlil. The benefits of the Basapa tradition for local residents, namely; development of the local economy. Then, as a momentum for the introduction of art and culture as well as beach tourism around the Ulakan Padang Pariaman area. Finally, the establishment of ukhuwah Islamiyah between the general public who follow the Basapa tradition and followers of the Syatariyyah order throughout West Sumatra and its neighboring areas, such as Riau, Jambi and others.